Gone with the Storm : Rainfall Shocks and Household Wellbeing in Guatemala - Baez, Javier E.; Lucchetti, Leonardo; Genoni, Maria E.; Salazar, Mateo (Taylor and Francis, 2017)
This paper identifies the negative consequences of the strongest tropical storm ever to strike Guatemala on household welfare. Per capita consumption fell in urban areas, raising poverty substantially. Households cut back on food consumption and basic durables, and attempted to cope by increasing their adult and child labour supply. The mechanisms at play include the intensity of the shock, food prices and the timing of Agatha with respect to local harvest cycles. The results are robust to placebo treatments, migration and measurement error, and partly explain the increase in poverty in the country previously attributed solely to the collateral effects of the global financial crisis.